Breastfeeding Supportive Services in Baby-Friendly Hospitals Positively Influenced Exclusive Breastfeeding Practice at Hospitalization Discharge and Six Months Postpartum - Lingling Li (MDPI AG, 2021)
Background: Studies have shown that implementing the Ten Steps to Successful Breastfeeding of the Baby-Friendly Hospital Initiative can protect, promote, and support breastfeeding. However, few studies have valuated the quality of breastfeeding supportive services provided by Baby-Friendly Hospitals from the perspective of service users. Methods: This was a hospital-based prospective study, conducted at eight Baby-Friendly Hospitals with a total of 707 pregnant women in Shanghai, China between October 2016 and September 2021. Breastfeeding supportive services during hospitalization were assessed at childbirth discharge using a 12-question questionnaire based on the Chinese “Baby-Friendly Hospital Evaluation Standards”. Women were followed up on six months postpartum. The impact of breastfeeding supportive services during hospitalization on the exclusive breastfeeding at discharge and six months postpartum were assessed. Results: Of the 707 mothers who completed the survey at discharge, 526 were followed up on six months after delivery. The overall exclusive breastfeeding rate among participants was 34.4% at discharge and 52.1% at six months postpartum. Mothers who received better breastfeeding supportive services during hospitalization were more likely to practice exclusive breastfeeding at hospitalization discharge compared with mothers who received poorer services (aOR: 3.00; 95% CI: 2.08, 4.35; p < 0.001). Furthermore, they were also more likely to exclusively breastfeed at six months postpartum (aOR: 1.50; 95% CI: 1.03, 2.22; p = 0.033). Conclusion: Better breastfeeding supportive services during hospitalization were significantly associated with higher rate of exclusive breastfeeding at discharge and six months postpartum. More effective measures should be adopted to improve the implementation of the breastfeeding supportive services in Baby-Friendly Hospitals to promote exclusive breastfeeding and better maternal and child health.